Transitory Spaces. Revitalization of the Cultural Landscape of the Vega de Granada - Arredondo Garrido, David (Estoa. Journal of the Faculty of Architecture and Urbanism, 2021)
The Vega de Granada (Spain) is a historical landscape of enormous value, from both productive and cultural points of view. In the last six decades, changes in the global economy, together with the permissiveness of the administrations with the urban growth on the rural realm, have deeply modified this territory. The contact spaces, those which materialize the rural-urban transition, seem able to revitalize this landscape in the 21st century. This article proposes to summarize the main crops grown here, as well as their architectural productions and infrastructures, that have shaped for centuries the cultural landscape of the Vega de Granada, starting from there, we will analyze the current situation of this territory, as well as some initiatives that are taking advantage of the lack of definition of those limit spaces, to try to recuperate local activities and valorize them. This article explains that these transitory spaces, activated by bottom-up initiatives, are the places with biggest possibilities to revitalize a cultural landscape without a clear future.